2018
DOI: 10.14198/jhse.2018.132.04
|View full text |Cite
|
Sign up to set email alerts
|

Physical demands of playing position within English Premier League academy soccer

Abstract: Physical demands of soccer competition vary between playing positions. Previous research investigated total, and high-speed distances, with limited research into acceleration demands of competition. Research investigating speed and acceleration demands have utilised arbitrary thresholds, overlooking the individual nature of athlete locomotion. The current investigation was the first utilising individual speed and acceleration thresholds, investigating the relative intensity of activities. Relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 29 publications
10
66
2
10
Order By: Relevance
“…The distinct activity profiles we observed by playing position are similar to those seen in other studies of youth elite soccer players 1 8 31 and adult professional soccer players 7 . This also applies to wide midfielders and center forwards covering the most distance at high speeds 4 8 20 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The distinct activity profiles we observed by playing position are similar to those seen in other studies of youth elite soccer players 1 8 31 and adult professional soccer players 7 . This also applies to wide midfielders and center forwards covering the most distance at high speeds 4 8 20 .…”
Section: Discussionsupporting
confidence: 87%
“…There are scarce data examining the peak running speed in elite youth soccer players despite the substantial practical applications such data may have on training prescription. In English Premier League academy players with a mean age of 19.9 years, the highest mean maximum speed was 31.0 km·h −1 , which was observed among wide attackers 1 . Al Haddad, Simpson, Buchheit, et al 3 observed a peak match speed of 26.8 km·h −1 in 60 elite U17 players, and when merging U13–U17 players in one pool, center forwards (n=52) were the fastest position at 27.0 km·h −1 .…”
Section: Introductionmentioning
confidence: 88%
“…On the other hand, we would also like to note that despite the observed differences (not always statistically supported) in the activity of individual posts (Di Salvo et al, 2007;Buchheit et al 2008;Bradley et al, 2009), we believe it is wrong for a collective game to go to individualizing the workload in positions, and it is right for the players to prepare for each of the types of motor activity. Some authors go further by placing individual load zones for each competitor (Abbott et al, 2018) In this respect, we support the opinion of Abt and Lovell (2009) and Siegel and Lames (2010) expressing the need to use individualised activity zones for individual age groups and, at the same time, the need for individual work zones for each competitor.…”
Section: Positional Differencessupporting
confidence: 84%
“…One of the most significant factors affecting the intensity of exercise load of sports game players is the player's position, with the observed differences being assessed as statistically significant (Abdelkrim, El Fazaa, & El Ati, 2007;Mathew & Delextrat, 2009;Vala & Litschmannová, 2012;Vala & Petr, 2013, Abbott, Brickley, & Smeeton, 2018.…”
Section: Resultsmentioning
confidence: 99%